Geology of the lujavrites from the Ilímaussaq alkaline complex South Greenland, with information from seven bore holes - Rose-Hansen, John; Sørensen, Henning (Meddelelser om Grønland. Geoscience, 2002)
Lujavrites, melanocratic agpaitic nepheline syenites, are the most highly evolved rocks of the Ilímaussaq alkaline complex, South Greenland. They have elevated contents of U. U-rich occurrences at Kvanefjeld in the northern part of the complex have been extensively drilled. Lujavrites from other parts of the complex were examined in seven bore holes, I to VII, in 1962 in an evaluation of the U potential of the complex. The study presents a general overview of the geology of the lujavrites, the distribution of various types of lujavrite and the structure of the complex partly based on the information obtained from the study of drill cores I-VII. The lujavrites are sandwiched between the roof and floor series of the complex. The drill cores penetrate the lower part of the roof series and present an incomplete section through the lujavrites. The lowermost lujavrites are dominated by aegirine lujavrites, cumulitic rocks directly succeeding the rocks of the floor series. The overlying arfvedsonite lujavrites intrude the lower part of the roof series. The alternation of aegirine- and arfvedsonite-bearing lujavrites and the formation of layering are interpreted to be caused by changes in the physico-chemical conditions of the lujavritic magma, especially changes in PH2O and fO2. Villiaumite, NaF, has only been found in drill cores from high levels in the complex. Naujakasite, which is a common constitutent of the hyper-agpaitic lujavrites at Kvanefjeld, has not been observed in drill cores I-VII. This may be linked to its formation at higher levels in the complex than represented by these drill cores. The lujavrites of bore holes I-VII have with few exceptions moderate contents of U.